2005
DOI: 10.1111/j.1528-1167.2005.31405.x
|View full text |Cite
|
Sign up to set email alerts
|

Photic‐ and Pattern‐induced Seizures: A Review for the Epilepsy Foundation of America Working Group

Abstract: Summary:Purpose: This report summarizes background material presented to a consensus conference on visually provoked seizures, convened by the Epilepsy Foundation of America.Methods: A comprehensive review of literature was performed.Results: Photosensitivity, an abnormal EEG response to light or pattern stimulation, occurs in ∼0.3-3% of the population. The estimated prevalence of seizures from light stimuli is ∼1 per 10,000, or 1 per 4,000 individuals age 5-24 years. People with epilepsy have a 2-14% chance o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
267
1
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 355 publications
(276 citation statements)
references
References 139 publications
4
267
1
4
Order By: Relevance
“…The key frequency to avoid is 15 Hz, which is given in prior art as the frequency with the greatest risk of seizures, with the risk decreasing linearly on either side. Further seizure risks not covered in this study include the color red, stripes, and alternating light and dark patterns [12]. All variance analyses performed on the data used p<0.05 as the probability level to accept statistical significance.…”
Section: Methodsmentioning
confidence: 99%
“…The key frequency to avoid is 15 Hz, which is given in prior art as the frequency with the greatest risk of seizures, with the risk decreasing linearly on either side. Further seizure risks not covered in this study include the color red, stripes, and alternating light and dark patterns [12]. All variance analyses performed on the data used p<0.05 as the probability level to accept statistical significance.…”
Section: Methodsmentioning
confidence: 99%
“…These frequencies were chosen due to: 1) our previous studies (Tello et al, 2014a;2014b;2014c) have shown that these generate strongest SSVEP responses; 2) safety recommendations specified in Fisher et al (2005); 3) studies conducted by Pastor et al (2003) about the relationship between visual stimuli and SSVEP-evoked amplitudes recommend these frequencies; 4) studies conducted by Herrmann (2001) showing peaks of SSVEPs at ∼15 Hz.…”
Section: Stimulation Unit (Su)mentioning
confidence: 99%
“…According to Drew et al (2001), lower frequency flickers generally produce more powerful constrictions, with color-dependence of flickers most visible between 3 and 6 Hz. In other study, Fisher et al (2005) show that flash and pattern reversal stimuli can provoke epileptic seizures especially in the 15-25 Hz range, but for some people, the upper limit of sensitivity can be as high as 65 Hz (Fisher et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Often the underlying disease is epilepsy, but at other times it may be a nonepileptic disorder that causes symptoms that resemble an epileptic seizure. 44 The term epilepsy encompasses a group of syndromes that vary in its associated pathology and seizure types. The diagnosis of the epileptic syndrome is one of the primary objectives undertaken when managing a patient with seizures.…”
Section: Epilepsy and Current Treatmentmentioning
confidence: 99%